Explaining positive deviance in public sector reforms in development - and Andrews, Matt (World Institute for Development Economic Research (UNU-WIDER), 2013)
Public sector reforms are commonplace in developing countries. Much of the literature about these reforms reflects on their failures. This paper asks about the successes and investigates which of two competing theories best explain why some reforms exhibi
Keywords: Development; Innovation; Reform; case survey; governance; growth; leadership